Deciphering Specificity Determinants for FR900359‐Derived Gqα Inhibitors Based on Computational and Structure–Activity Studies. (3rd July 2018) - Reher, Raphael; Kühl, Toni; Annala, Suvi; Benkel, Tobias; Kaufmann, Desireé; Nubbemeyer, Britta; Odhiambo, Justin Patrick; Heimer, Pascal; Bäuml, Charlotte Anneke; Kehraus, Stefan; Crüsemann, Max; Kostenis, Evi; et al.
Abstract: Direct targeting of intracellular Gα subunits of G protein‐coupled receptors by chemical tools is a challenging task in current pharmacological studies and in the development of novel therapeutic approaches. In this study we analyzed novel FR900359‐based analogs from natural sources, synthetic cyclic peptides, as well as all so‐far known Gq α inhibitors in a comprehensive study to devise a strategy for the elucidation of characteristics that determine interactions with and inhibition of Gq in the specific FR/YM‐binding pocket. Using 2D NMR spectroscopy and molecular docking we identified unique features in the macrocyclic structures responsible for binding to the target protein correlating with inhibitory activity. While all novel compounds were devoid of effects on Gi and Gs proteins, no inhibitor surpassed the biological activity of FR. This raises the question of whether depsipeptides such as FR already represent valuable chemical tools for specific inhibition of Gq and, at the same time, are suitable natural lead structures for the development of novel compounds to target Gα subunits other than Gq . Abstract : Determining binding determinants : FR9003590 and YM‐254890 are currently the most potent Gq inhibitors known. We report why it is so difficult to improve their potency based on novel FR900359 derivatives and in comparison to all analogs in current use. In a combined structural and computational study, we identify the binding determinants for these inhibitors in their specific binding pocket on the Gq protein.